264 Incorporating Neurolinguistics and the Role of Speech and Language Therapy in a Specialist Memory Service. (16th September 2019) - Sheridan, Lisa; McHale, Cathy; Dookhy, Joshi; Coughlan, Tara; O'Neill, Desmond; Collins, Ronan; Ryan, Dan; Kennelly, Sean
Abstract: Background: Speech and Language Therapy (SLT) is recognised as having a unique role in contributing to the overall neuropsychological assessment of people living with dementia and cognitive impairment. The role of the SLT within a memory clinic has become more widely understood. It is now recognised that speech and language characteristics are reported to be amongst the most reliable behavioural markers for distinguishing amongst different dementia subtypes, and specific analysis of a language production and delivery facilitates timely and more accurate diagnosis. Methods: Patients with a language predominant presentation or those with subjective complaints of speech/language difficulties were referred for SLT assessment through the tertiary memory assessment and support service from January 2018 – March 2019. Assessment of speech and language skills, and overall cognitive communications skills were reviewed, and this information was used to aid with differential diagnosis and contribute to the person's overall cognitive profile. The SLT attends weekly memory service interdisciplinary consensus diagnosis conference. Data was collected on these patients to observe the profiles of those patients referred to SLT. Results: 22 patients were seen for full SLT assessment during this period, 13 women, 9 men; mean age 69.5 (range 48- 80). Diagnoses include: AD (32%), FTD behavioural variant (14%), Primary Progressive Aphasia (14%), Non-amnestic MCI (18%), Amnestic MCI (14%), Other neurological disorder (8%). 68% of these patients required ongoing SLT intervention for their cognitive communication difficulties following diagnosis. Conclusion: SLTs fulfil an integral role in supporting both the diagnostic and post-diagnostic care pathways of people living with dementia and cognitive impairment attending memory services. SLTs have a unique role and skillset in identifying the specific nature of language difficulties for a person with dementia or cognitive impairment and in reducing the impact of the communication difficulties for the person and for their family members.